A NOD FACTOR BINDING PROTEIN FROM LEGUME ROOTS - ETZLER, MARILYNN E; MURPHY, JUDITH B (1999)
The present invention provides NBP46 polynucleotides that are useful in modulating Nod factor binding and other plant functions.